Особливості методології порівняльних педагогічних досліджень - Світлана Цюра (Pavlo Tychyna Uman State Pedagogical University, 2013)
Узагальнено дані вітчизняних та зарубіжних компаративних педагогічних досліджень, розглянуто методологію порівняльного аналізу як конкретно-наукову, виокремлено низку її теоретичних концептів, принципи та підходи до організації дослідження, уточнено особливості технології, завдання конструктивістського компаративного педагогічного пошуку. Обобщено данные отечественных и зарубежных компаративных педагогических исследований, рассмотрено методологию сравнительного анализа в качестве конкретно-научной, выделено ряд ее теоретических концептов, принципы и подходы к организации исследования, уточнены особенности технологи, задачи конструктивистского педагогического поиска. The problems of methodology of comparative analysis and the necessity of its reconsideration are in the focus of attention of numerous native and foreign scholars. The main of them is to work out methodology of comparative research deeper than homotypic educational phenomena which developed independently within different sociocultural systems. The study of phenomena and processes in interrelations and interdependence with «the common», its cultural-historic background and accents on evolutional and self-organizing character of educational changes replaced the descriptive approach of «the foreign». The systematized survey of the sources on comparative pedagogical analysis let us distinguish four approaches to the organization of investigation. Historical-comparative (vertical or horizontal), comparative-historical (horizontal-vertical or vertical) belong to comparative ones and are based on «geographical criterion» when this or that «foreign» country is analyzed. The more popular typical comparative approaches based on «subjective criterion» presuppose geographic, judicial, axiological, mental belonging of a researcher to one of the cultures for the sake of which the analysis is carried out. Modern constructivist comparative approaches are directed away from simple statements of conditions and suggest development, reconstruction or new interpretation, when a researcher being «non-product» of an analyzed system is able to provide an independent evaluation of efficiency of processes as opposed to its axiologically-committed subjects. In the perspective one-object researches turn into two- and poly-object ones based on the principles of a system approach; unity of purposes and goals of education in world practice and propriety of technological variation; priority of development of educational systems with the focus on human values; coincidence of vectors directed on a part and on the whole in the evolution of pedagogical empirism (school, educational system of a country, regional, world educational space).